2003
DOI: 10.1097/01.ju.0000081095.85420.ab
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predictive of Urinary Retention After a Tension-Free Vaginal Tape Procedure for Female Stress Urinary Incontinence

Abstract: An accurate measurement of the peak urinary flow rate could predict women at risk for postoperative urinary retention that compromises global satisfaction after the highly curative TVT procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
5
9

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(91 citation statements)
references
References 16 publications
6
71
5
9
Order By: Relevance
“…A prospective trial of 89 women who underwent the midurethral sling procedure showed low peak flow rate to be the only independent variable for a successful initial voiding trial (16). This is consistent with another retrospective study of 375 patients by Hong et al (17), which also found lower preoperative peak flow rates as a risk factor. In this study, the parameter for VD was defined as the need to catheterize for 72 hours or longer after surgery.…”
Section: Urodynamic Parameterssupporting
confidence: 80%
See 1 more Smart Citation
“…A prospective trial of 89 women who underwent the midurethral sling procedure showed low peak flow rate to be the only independent variable for a successful initial voiding trial (16). This is consistent with another retrospective study of 375 patients by Hong et al (17), which also found lower preoperative peak flow rates as a risk factor. In this study, the parameter for VD was defined as the need to catheterize for 72 hours or longer after surgery.…”
Section: Urodynamic Parameterssupporting
confidence: 80%
“…CISC is performed three or four times daily until the residual decreases to less than 100 ml, or at most 50% of the voided volume (37). Although several reports have shown some benefit with urethral dilatation (17,38), recent reports have proven urethral dilation to be ineffective in most patients with urethral obstruction after TVT procedures. Additionally, repeated urethral dilation may predispose to the development urethral erosion and could induce scarring of the urethra (24,39,40).…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…19,20 The mean age of patients both with and without voiding difficulty was less than 60 in each study. Sevestre et al 21 reported the cure rate of TVT in 76 women over 70 years of age as 67% but provided no comparison data from younger women.…”
Section: Discussionmentioning
confidence: 86%
“…18 Pre-operative urodynamic variables have been evaluated to assess their predictive value in postoperative voiding dysfunction. [19][20][21][22] The risk of bladder injury is considerably lower, less than 1% with the transobturator approach, but it does exist and hence Cystoscopy should be considered in TOT procedures as well. 23 The risk of urethral perforation with needle passage in transobturator space is 0.1-2.5%.…”
Section: Discussionmentioning
confidence: 99%